A chart review tool to systematically assess the safety of prehospital care for children with out‐of‐hospital cardiac arrest. Issue 3 (29th April 2022) - Schoonover, Amanda; Eriksson, Carl O.; Nguyen, Thuan; Meckler, Garth; Hansen, Matthew; Harrod, Tabria; Guise, Jeanne‐Marie
Abstract: Objective: Create an easy‐to‐use pediatric out‐of‐hospital cardiac arrest (OHCA)‐specific chart review tool to reliably detect severe adverse safety events (ASEs) in the prehospital care of children with OHCA. Methods: We revised our previously validated pediatric prehospital adverse event detection system (PEDS) tool, used to evaluate ASEs in the prehospital care of children during emergent calls, to create an OHCA‐specific chart review tool. We developed decision support for reviewers, reviewer training, and a dedicated section for chart data abstraction. We randomly selected 28 charts for independent review by 2 expert reviewers who determined the presence or absence of a severe ASE for each care episode and identified the domain of care and preventability for each ASE. We calculated inter‐rater agreement in the assessment of the presence or absence of a severe ASE using Gwet's first‐order agreement coefficient (AC1). Results: The PEDS‐OHCA chart review tool has 6 sections, with a minimum of 70 and maximum of 667 total possible fields. We found inter‐rater agreement of 0.83 (95% confidence interval, 0.63–0.99) between our 2 reviewers for the overall detection of a severe ASE and an average time to complete of 8 minutes (range, 2–25 minutes). Inter‐rater agreement in the detection of a severe ASE in each individual domain ranged from 0.36 to 0.96. Conclusions: The PEDS‐OHCA is the first chart review tool to systematically evaluate the safety and quality of EMS care for children with OHCA. This tool may help improve understanding of the quality of EMS care for children with OHCA, which is essential to improving outcomes.